2010
DOI: 10.1017/s1355770x10000392
|View full text |Cite
|
Sign up to set email alerts
|

Collective action for watershed management: field experiments in Colombia and Kenya

Abstract: Edición, diseño de cubierta, preprensa y prensa digital: Proceditor ltda. Calle 1C No. 27 A -01 Bogotá, D. C., Colombia Teléfonos: 2204275, 220 4276, Fax: extensión 102 proceditor@etb.net.co Impreso en Colombia -Printed in ColombiaEl contenido de la presente publicación se encuentra protegido por las normas internacionales y nacionales vigentes sobre propiedad intelectual, por tanto su utilización, reproducción, comunicación pública, transformación, distribución, alquiler, préstamo público e importación, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 20 publications
6
63
1
4
Order By: Relevance
“…Hackett et al (1994) and Holahan (2011) examine CPR settings where subjects have communication or voting opportunities to facilitate cooperation, where subjects receive differential returns from agreements that are linked to the capacity to appropriate. Cardenas et al (2011) and Janssen et al (2012) examine settings where CPR users face sequential decisions, introducing asymmetries through the position (order) each subject has in making appropriation decisions. translation of instructions), a consent form, and instructions for each of the decision settings with subject-specific parameters.…”
Section: The Experimental Decision Settingmentioning
confidence: 99%
“…Hackett et al (1994) and Holahan (2011) examine CPR settings where subjects have communication or voting opportunities to facilitate cooperation, where subjects receive differential returns from agreements that are linked to the capacity to appropriate. Cardenas et al (2011) and Janssen et al (2012) examine settings where CPR users face sequential decisions, introducing asymmetries through the position (order) each subject has in making appropriation decisions. translation of instructions), a consent form, and instructions for each of the decision settings with subject-specific parameters.…”
Section: The Experimental Decision Settingmentioning
confidence: 99%
“…This is consistent with the findings of Kimbrough and Vostroknutov (2015) in a lab experiment using students. Similar studies which found exhaustion of resources under different growth treatments include the Forestry Game by Cardenas et al (2011), andBru et al (2003).…”
Section: Discussionsupporting
confidence: 53%
“…Some important aspects covered in previous studies include the effects of economic and social heterogeneities (Taylor and Singleton 1993;Agrawal 1998;Varughese and Ostrom 1998;Kimbrough and Vostroknutov 2015), subjective satisfaction on the CPR games over standard measures of objective behavior of players (Becchetti et al 2016), impatience and cooperation (Schlager and Heikkila 2009), asymmetry in field experiments on CPR problems (Fehr and Leibbrandt 2011;Cardenas et al 2011;Janssen et al 2011), the influence of different institutional arrangement on CPR extraction (Cardenas and Ostrom, 2004;Rodriguez-Sickert et al 2008;Cardenas et al 2011), culture and ecology on cooperation (Sebastian et al 2011), social norms and ecological variables on cooperation and sustainable management of CPRs (Ostrom 2009;Lo 2013;Kimbrough and Vostroknutov 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive empirical studies have helped to build theories of collective action and improve our knowledge of conditions influencing collective action in communities and their ability to self-organize and govern local resources [24,25,32,33]. Scholarship on various institutional arrangements and their influence on collective action outcomes in commons resources exists in the literature, including forestry [34,35], fisheries [32,36,37], watershed [38][39][40], and multiple-resources governance [12,32,[41][42][43]. Multiple contexts and process variables that potentially influence outcomes of co-management, either positively or negatively, have been identified by empirical and meta-analyses, as highlighted in Table S1 [12,13,19,27,30,44,45].…”
Section: Co-management: a Retrospectmentioning
confidence: 99%